Neisseria meningitidis native outer membrane vesicles containing different lipopolysaccharide glycoforms as adjuvants for meningococcal and nonmeningococcal antigens. - Nagaputra, J; Rollier, C; Sadarangani, M; Hoe, J; Mehta, O; Norheim, G; Saleem, M; Chan, H; Derrick, J; Feavers, I; Pollard, A; Moxon, E (2014)
We evaluated the adjuvant effect of a modified glycoform of lipopolysaccharide (LPS) (LgtB-LpxL1) compared to that of the nonmodified glycoform Lpxl1 serogroup B meningococcal H44/76 native outer membrane vesicles (nOMVs) on immune responses to vaccination with the recombinant meningococcal protein, rPorA, tetanus toxoid, or meningococcal serogroup C capsular polysaccharide. We used LgtB-LpxL1 LPS because the disruption of the lgtB gene, which results in the exposure of N-acetylglucosamine-galactose-glucose residues in the LPS outer core, has been shown to enhance the activation of human dendritic cells in vitro. The responses were compared to those of a monophosphoryl lipid A (MPL)-based adjuvant and to an aluminum hydroxide suspension. The nOMVs induced blood serum IgG responses against each of the three antigens comparable to those obtained with MPL or aluminum salt. However, nOMVs elicited (i) a lower IgG1/IgG2a ratio against rPorA and (ii) serum bactericidal antibody titers superior to those achieved with aluminum salt, reaching similar titers to those obtained with MPL. Similarly, bactericidal antibody titers induced by immunization with meningococcal serogroup C polysaccharide and nOMVs were similar to those obtained using MPL but were better than those with aluminum salt. Immunization with tetanus toxoid and nOMVs resulted in tetanus toxoid-specific IgG responses similar to those obtained when adjuvanted with aluminum salt. These results highlight the potential utility of meningococcal LpxL1 LPS-containing nOMVs as an adjuvant for recombinant meningococcal protein vaccines and suggest their possible use with a variety of other antigens.